Analisis penerapan 5s ditinjau dari perspektif guru dan peserta didik sekolah dasar - Nugraheni Sekar Enggarjati; Siti Istiyati (Universitas Sebelas Maret, 2025)
This study aims to describe the application of the 5S culture (Salam, Senyum, Sapa, Sopan, Santun) from the perspective of teachers and fifth grade students at SD Negeri Jajar Kota Surakarta. This research is a descriptive qualitative research. Sources of research data include class teachers, principals, and students. The sampling technique was done by purposive sampling. Data collection was done by observation, interview, and questionnaire. The validity test technique used was triangulation technique and source. Data analysis used in this research uses 4 stages according to Miles and Hubberman, namely data collection, data reduction, data presentation, and verification. The implementation of 5S in SD Neger Jajar Surakarta City shows the tendency of sopan to get the highest percentage of (50.27%), followed by santun (48.74%), salam (36.47%), senyum (32.35%), and sapa (26.47%). However, the behavior of students does not fully reflect the application of 5S because there are still inappropriate attitudes such as speaking rudely, being disorderly, and lack of respect for others. This finding shows that the application of 5S has not been optimal and requires continuous habituation and cultivation